Cooperative longevity of interaction model for addressing paused handoff problem in smart city intelligent transportation systems - Abdullah Faiz Al Asmari; Tariq Alqubaysi; Fayez Alanazi; Ahmed Almutairi; Ammar Armghan (PLoS ONE, 2025)
Smart cities use Intelligent Transportation Systems (ITS) to manage traffic by continuously communicating with roadside infrastructure and nearby vehicles. Paused handoff interrupts grounded congestion, signal supervision, and path-shifting knowledge. Paused handoffs occur when cars wait to interact owing to volatile neighbours or heavily crowded roadside units. In congested metropolitan areas, ITS vehicle communication interruptions are a significant issue. This research addresses this issue. Hence, the research introduces the Cooperative Longevity of Interaction Model (CLoIM) to enhance communication reliability by minimizing the impact of paused handoff. The model employs a hybrid trained herd optimization algorithm to improve the longevity for interaction between vehicles and roadside units, minimizing handoff interruptions. The approach dynamically adjusts search strategies to prioritize high longevity interactions, improving communication stability. Results show that CLoIM increases longevity by 10.81% and reduces the paused handoff lag by 9.17%, effectively addressing the challenges of vehicle density and mobility in ITS scenarios.